Robotics Dexterous Grasping: The Methods Based on Point Cloud and Deep Learning - Duan, Haonan; Wang, Peng; Huang, Yayu; Xu, Guangyun; Wei, Wei; Shen, Xiaofei (Frontiers in Neurorobotics, 2021)
Dexterous manipulation, especially dexterous grasping, is a primitive and crucial ability of robots that allows the implementation of performing human-like behaviors. Deploying the ability on robots enables them to assist and substitute human to accomplish more complex tasks in daily life and industrial production. A comprehensive review of the methods based on point cloud and deep learning for robotics dexterous grasping from three perspectives is given in this paper. As a new category schemes of the mainstream methods, the proposed generation-evaluation framework is the core concept of the classification. The other two classifications based on learning modes and applications are also briefly described afterwards. This review aims to afford a guideline for robotics dexterous grasping researchers and developers.